Parallel multibody separation simulation using MPI and OpenMP with communication optimization. (September 2018) - Ma, Wenpeng; Hu, Xiaodong; Liu, Xiazhen
In this paper we investigate parallel implementations of multibody separation simulation using a hybrid of message passing interface and OpenMP. We propose a mesh block-based overset communication optimization algorithm. After presenting details of local data structures, we present our strategy for parallelizing both the overset mesh assembler and the flow solver by employing message passing interface and OpenMP. Experimental results show that the mesh block-based overset communication optimization algorithm has an advantage in real elapsed time when compared to a process-based implementation. The hybrid version shows that it is suitable for improving the load balance if a large number of CPU cores are used. We report results for a standard multibody separation case.